2017
DOI: 10.1515/gse-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation in Treatment of Swine Slaughterhouse Wastewater

Abstract: In this study, wastewater taken from the Nam Phong swine slaughterhouse, Ho Chi Minh City, was used to evaluate the treatment efficiency of common coagulants, including Alum (Aluminum Sulfate -Al2(SO4)3.18H2O), Poly-Aluminum Chloride (PAC), and Ferrous Sulfate (FeSO4.7H2O), using a jartest system. The experiments were conducted using the one-factor-at-a-time method to examine three variables which are pH, stirring speed, and coagulant dosage. The results showed that both Alum and PAC perform over 90% removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…This indicates the effectiveness of the process in improving effluent quality by obtaining around 60% additional removal of COD compared to sedimentation. These results quite agree with what other authors report who indicate that the coagulation using ferrous ion reaches the maximum efficiency at pH between 8 and 11, because in these pH ranges ferrous ions mainly exist in the form of Fe(OH) 2 and show effectiveness in treatment (Ha & Huong 2017;Gökçek & Özdemir 2020).…”
Section: Analysis and Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates the effectiveness of the process in improving effluent quality by obtaining around 60% additional removal of COD compared to sedimentation. These results quite agree with what other authors report who indicate that the coagulation using ferrous ion reaches the maximum efficiency at pH between 8 and 11, because in these pH ranges ferrous ions mainly exist in the form of Fe(OH) 2 and show effectiveness in treatment (Ha & Huong 2017;Gökçek & Özdemir 2020).…”
Section: Analysis and Resultssupporting
confidence: 93%
“…There are several reports from researchers about slaughterhouse wastewater treatment, containing less than 4.0 g/L of COD, via coagulation-flocculation using different reagents, reaching high efficiencies of organic matter removal (70-80% COD removal). Nevertheless, the concentrations of other parameters are still high, for example turbidity, color, or suspended solids, which implies requiring other treatment steps (Ha & Huong 2017;Gökçek & Özdemir 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The best removal efficiency (75.4%) was observed at pH 6.9 which is similar to Guida et al [15] where the COD was removed effectively using alum at a pH between 6 to 8. Another study by Ha and Hong [19] also showed that the best performance of alum is in a neutral environment. When the pH increased to higher than 8, the COD removal efficiency decreased slightly and reached a 50.8% removal at pH 9.9.…”
Section: Dosage Of Tannin (Ml)mentioning
confidence: 91%
“…Amuda et al [17] indicated that the optimum dosage for the removal of Cr, Fe, and Zn from leachate by ferric chloride was 0.5 g/L. Also, Bui et al [23] indicated that the optimum dosage for color, turbidity, COD, and total phosphorus removal from slaughterhouse wastewater by PAC was 0.550 g/L. In another study, Wang et al [31] obtained the best results for COD and Total Suspended Solids (TSS) removal at 0.5 g/L by ferrous sulfate and alum.…”
Section: Removal Efficiency At Distinct Coagulant Dosesmentioning
confidence: 99%
“…Subsequently, the pH of the solution is one of the considerable parameters in wastewater treatment by coagulants. Low or high pH values can influence treatment proficiency; then, deciding the ideal pH values is fundamental [23]. The experiments for ideal pH were completed at 100 ml of the plating wastewater at various estimations of 1.5, 3, 5, 7, 9, and 11, at a temperature of 25 °C, blended speed of 300 rpm for 1 min and 150 rpm for 15 min, settlement time of 40 minutes, and coagulant dose of 0.1g.…”
Section: Removal Efficiency At Different Ph Valuesmentioning
confidence: 99%